2000
DOI: 10.1097/00004714-200010000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Mirtazapine Effects on Alertness and Sleep in Patients as Recorded by Interactive Telecommunication During Treatment With Different Dosing Regimens

Abstract: This double-blind study compared mirtazapine's effects on alertness and sleep between parallel groups treated for 2 weeks according to a fixed regimen of 30 mg at bedtime (N = 69) and one that increased in dose from 15 to 30 mg at bedtime after the first week (N = 71). These patients with depression used an interactive telephone/computer system for daily alertness and sleep recordings on self-rating scales before and during treatment. Efficacy (17-item Hamilton Rating Scale for Depression [HAM-D], Clinical Glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
30

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 12 publications
1
31
0
30
Order By: Relevance
“…This dosage regimen facilitated and increased sleep efficiency and improved depression, but did not affect daytime alertness or motor performance. 39 Graves & Napier 40 found that chronic dosing with MIR did not alter motor performance in a rat study. We recently reported that chronic MIR dosing (30 mg/kg for 30 consecutive days) did not alter spontaneous locomotor activity in rats.…”
Section: Experiments 2: Effect Of Chronic Mir Dosing On Sedationmentioning
confidence: 98%
See 1 more Smart Citation
“…This dosage regimen facilitated and increased sleep efficiency and improved depression, but did not affect daytime alertness or motor performance. 39 Graves & Napier 40 found that chronic dosing with MIR did not alter motor performance in a rat study. We recently reported that chronic MIR dosing (30 mg/kg for 30 consecutive days) did not alter spontaneous locomotor activity in rats.…”
Section: Experiments 2: Effect Of Chronic Mir Dosing On Sedationmentioning
confidence: 98%
“…15,38 Radhakishun et al 39 reported that MIR treatment with initial doses of 15 mg/kg subsequently increased to 30 mg/kg for several weeks was well tolerated, with only 10% of patients reporting adverse effects during the first week and fewer patients doing so in subsequent weeks. This dosage regimen facilitated and increased sleep efficiency and improved depression, but did not affect daytime alertness or motor performance.…”
Section: Experiments 2: Effect Of Chronic Mir Dosing On Sedationmentioning
confidence: 99%
“…A USPSTF és az American College of Physicians (ACP) ajánlásai szerint minden elhízott pácienst életmód-változtatási -elsősorban diétára és testmozgásra vonatkozó -tanáccsal kell ellátni (33,38). Ennek ellenére még akkor is, ha az elhízott be-2006 ■ 147. évfolyam, 13. szám ORVOSI HETILAP 3. ábra: A túlsúlyos, ill. elhízott beteg kivizsgálása ACTH = adrenokortikotrop hormon; GH = növekedési hormon; IGF = inzulinszerű növekedési faktor teg egészségügyi ellátásért folyamodik, csak 27-42% -uknak javasolják a testsúlycsökkentést (18,19). Amennyiben a BMI nem haladja meg a 25 kg/m2-t, cél a testsúly megtartása, a súlygyarapodás elkerülése, melyet az egészséges életvitel pozitív megerősítésével kell biztosítani.…”
Section: Találkozás Az Elhízott Beteggelunclassified
“…Ismert, hogy a HCV-fertőzött egyének NK-sejtjeire fokozott CD94-NKG2A-expresszió, TGFß-és IL-10-termelés jellem ző, amely révén csökkent mértékben képesek dend riticus sejtek aktivációjára (20). A krónikus C-hepatitisben észlelt károsodott NK-aktivitás (32) hátteré ben egyrészt a HCV-core protein általi MHC I mole kula indukció (19), másrészt a HCV-E2 fehérje és az NK-sejteken expresszálódó CD81 molekula kereszt kötése általi NK-sejt-aktiváció gátlása állhat (9,43).…”
Section: Az Immunválasz Jellemzői Hcv-infekcióbanunclassified
See 1 more Smart Citation